EFEITO DA MODIFICAÇÃO TÉRMICA NAS PROPRIEDADES TECNOLÓGICAS DA MADEIRA DE EUCALIPTO PARA DECK - Andrade, Jaily Kerller Batista de (2021)
Considering the diversity of tropical woods present in Brazil, which are used commercially, few species are used for the production of floors, especially for decks. As result of the disorderly exploitation of native tropical species, wood from reforestation, especially those of the Eucalyptus genus, has been used in order to attend the demand. However, some properties of these woods need to be improved; thus, suggest the thermal treatments, which can add qualities in order to serve the market. This research aims to evaluate the effects of heat treatment on the technological properties of wood from 14-year-old Eucalyptus hybrid clones for deck production. For this purpose, three clones (A, C and E), two wood heat treatment temperatures (185 and 200 °C) and the control were used. Tests were carried out on colorimetry, chemical, physical and mechanical characterization, surface finish and stain adhesion, screw-holding and resistance to the impact of the falling sphere and the effect of accelerated aging on the color of the wood. The thermal treatments promoted the darkening and uniformity of the color of the evaluated clones, as well as positive changes in the physicochemical properties, without relevant changes in the evaluated mechanical properties. They also did not negatively influence the adhesion and fixation of the stain, with the finished woods having better resistance to artificial weathering. Thus, the heat treatment at 185 °C, for wood from eucalypts clones, and clone A, promoted better changes in resistance to accelerated aging, color uniformity and in the chemical, physical and mechanical properties of the wood, allowing its use on floors with low circulation, such as decks.